DYNAMIC STABILITY IN THE CHANGEABLE WORLD AND ITS LEGAL PROVISION - K. Duyunov, Vladimir; V. Zakomoldin, Ruslan; P. Butenko, Tat’yana; R. Galoyan, Arpenik (Gênero & Direito, 2020)
The work aims at analyzing the issues of legal provision of social stability as a prerequisite of global and national safety under the changeable conditions of the contemporary world order. To this end, the authors analyze the Strategy of National Safety of the Russian Federation, approved by the Russian President in 2015, the data of sociological research of 2015–2018, statistical data, and special literature. As a result, the common notion of stability is formulated, its varieties are distinguished, features and meaning are determined. The necessity for harmonious combination of stability and changeability is highlighted. The importance of law in providing stability is emphasized. The modern trend of perpetual growth of the number of laws is criticized, as it results in the decrease of their quality, systemic character and steadiness of legislation. The conclusion is made that the key factor of providing safety is dynamic stability – a harmonious combination of stability and dynamism of all social processes.